Modelagem e controle de corpo completo de um manipulador aéreo - Laysa Santos Mello (2015)
This dissertation presents the modeling and control of whole-body of aerial manipulator, composed of a quadrotor UAV coupled to a manipulator. The modeling is based on the algebra of dual quaternions to and diferential and forward kinematic models of the heterogeneous serially coupled chain. The dynamic model, obtained from the Euler-Lagrange formulation (which uses the kinematic model), expresses the inuence of the manipulator's movement in the system's center of mass. The presented control laws are developed for the aerial manipulator tracks the desired trajectory in the end-efectors level, while keeping the system stable even in the presence of external disturbances, parametricuncertainties and unmodeled dynamics. Three types of controllers are proposed, which all of them with a cascading control structure formed by two levels. In the first case, it has a kinematic controller in the outer loop and an inverse dynamics controller in the inner loop. The inverse dynamics controller is modified, having in its outer loop a kinematic controller in the task space, which is the space where it performs the task. In the second case, there is a similar controller with the first are, but the inner loop controller is obtained from feedback linearization. Finally, in the third case, there is the H1 linear controler of the outer loop's kinematic model, and in the inner loop, the inverse dynamics controller. The performance of the proposal control strategies is evaluated through simulation and the results had shown acceptable, because it caught up with the objectives of the controllers, who were tracking the trajectory with errors considered small compared to the scale of trajectories. This validates the whole-body modeling techniques based on dual quaternion algebra, that leave the uid and continuous movements and control techniques for underactuated and nonlinear system.